Natural product extract fractions as potential arthritis treatments: A detailed analysis using in-silico, in-vivo, and in-vitro methods - Bharathiraja Anthony Samy (22282423) (2024)
Two characteristics of the systemic autoimmune disease rheumatoid arthritis (RA) include extra-articular involvement and inflammatory arthritis. It is a long-term inflammatory condition that mostly affects the synovial joints and is often triggered by a confluence of environmental factors, including tobacco use, and genetics. The review investigates natural products’ role in arthritis through three key approaches. In-silico analysis identifies molecular mechanisms and targets of these products, revealing their potential for therapeutic use. In-vivo studies evaluate how well these products work and their safety in reducing joint inflammation. in-vitro studies focus on how these compounds interact at the cellular level and their effects on signaling pathways. Together, these approaches offer a comprehensive understanding of how natural products could benefit arthritis management. This review focuses on translational studies and highlights the possible role of natural compounds as adjunctive therapies to conventional arthritis treatments. In conclusion, this study indicates that natural products have potential advantages in treating osteoarthritis and rheumatoid arthritis based on In-silico analysis which shows anti-inflammatory effects, in-vivo studies that reduce joint inflammation, and in-vitro studies that amplify arthritis management. To improve the therapeutic advantages of natural products utilized for treating arthritis, an all-inclusive examination has been done to give direction for the following research efforts. Other Information Published in: International Immunopharmacology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.intimp.2024.113595